Exosomal hsa_circ_0008925 from Urine Is Related to Chronic Renal Fibrosis. (18th February 2022) - Cao, Yuhan; Shi, Yuanhui; Wang, Yuwei; Yang, Yanlang; Guo, Wenjun; Zhang, Cuifeng; Pei, Wenjun; Fu, Cong
Abstract : At present, there is no noninvasive biomarker of renal fibrosis. The potential diagnostic value of urinary exosome-derived circRNAs from glomerular disease patients for renal fibrosis is still uncertain. Here, we first detected the expression of hsa_circ_0008925 in TGF- β 1-cultured HK-2 cell-derived exosomes. Secondly, we collected urine samples from 95 biopsy-proven glomerular disease patients and 34 healthy controls. The expression of hsa_circ_0008925 was analyzed, and the correlation with renal function and pathological changes was calculated. The receiver operating characteristic (ROC) curve for the diagnosis of renal fibrosis was performed. The results showed that in exosomes derived from TGF- β 1-cultured HK-2 cells, the expression of hsa_circ_0008925 was increased compared with normal cultured. Further, the expression level of hsa_circ_0008925 was increased in urinary exosomes from renal fibrosis patients and correlated with serum creatinine, blood urea nitrogen (BUN), estimated glomerular filtration rate, and cystatin C. The level of hsa_circ_0008925 was furthermore correlated with the score of tubulointerstitial fibrosis (TIF) and the score of glomerular sclerosis. The ROC curve showed that hsa_circ_0008925 can diagnose renal fibrosis at a cut-off value of 0.093 with a sensitivity of 52.2% and specificity of 96.4%. In summary, we indicated that urinary exosomal hsa_circ_0008925 could be acted as a noninvasive biomarker for renal fibrosis in glomerular diseases patients.